MACEDONIAN CHILDREN′S LITERATURE IN THE XIX CENTURY (Philological Studies, 2021)
The text will follow the appearance of the first children's works in the Macedonian literary XIX century. Their significance, despite the fact that they do not have high aesthetic values, is nevertheless great, because they responded to the needs of the time. Furthermore, they give us the opportunity to determine the continuity of development of Macedonian children's literature, which has primary importance for the mental, emotional and educational development of children. We note, especially in the last few years, that the interest for children's literature is great, both by authors and by publishers, who have started republishing works. This confirms the universality of children's literature, with its timeless themes and motives which are interesting, intriguing, attractive, fun, fulfilling their ultimate pedagogical function, directing the child towards better life principles.Up until the Enlightenment, there was no interest in the child, except for the solitary manifestations by John Locke, Jan Amas Komensky and Jean-Jacques Rousseau. A real interest in the child was shown in the time of Romanticism. Within the Macedonian cultural development there is an interest shown in children during the Enlightenment, at the beginning of the XIX century. The first books published in the vernacular were intended for adults, but at the same time provided directions for better upbringing of children. The first authors of children's works, among the series of their activities, were collectors of folk art who were also engaged in education. Authors of the so far discovered works for children are Partenija Zografski, Jordan Hadzi Konstantinov Dzinot, Grigor Prlichev, Evtim Sprostranov, Tomo Sminjanic Bradina, and we will also acknowledge Marko Cepenkov.